Findings Between the Sensitive and the Tangible: A Comparison of the Casting Methods for 925 Silver Used by Costa Rican Artisans - Cavallini, Hennia (2021)
This paper presents the research product based on the artisanal production of silver alloys, where the casting process and the common variables used by artisan goldsmiths are considered. This is a research focused on the artisans’ experiences, which has the purpose of showing, from the analysis of samples, the complexity of these processes, as well as the degree of technical improvement achieved by goldsmith artisans in their practice and development of their sensitivity in working with materials. The foregoing, not to validate the craftsman’s practices from science; rather, to draw link paths that allow mutual benefit. We worked with three samples of silver alloys generated from artisan processes. Scanning electron microscopy (SEM) and X-ray techniques were used for the analysis. This reveals the effect that the use of oxyacetylene, oxypropane, and electric furnace can generate in the casting process, its advantages, and its disadvantages.